Evaluation of long-term bond strength and selected properties of self-adhesive resin cements - Carianne Mendes de ALMEIDA; Carine Tais Welter MEEREIS; Fernanda Barbosa LEAL; Aline Oliveira OGLIARI; Evandro PIVA; Fabrício A OGLIARI (Sociedade Brasileira de Pesquisa Odontológica, 2018)
Abstract This study evaluated the shear bond strength (SBS) of self-adhesive resin cements (SARCs) to dentin and their physical-chemical properties. Five commercial SARCs were evaluated [SmartCem®2 - DENTSPLY (SC2); BisCem® - Bisco (BC); SeT PP® − SDI (SeT); Relyx U100® - 3M ESPE (U100) and YCEM® SA - Yller (YCEM)]. The SARCs were evaluated for SBS to dentin (n = 10) after 24 h, 6 months, and 12 months. The dentin demineralization caused by acidic monomers was observed by SEM, and pH-neutralization of eluate was observed for 24 h. Degree of conversion (DC), rate of polymerization (Rp), flexural strength (FS), and elastic modulus (E) were evaluated. Immediate SBS of SC2, SET, U100, and YCEM were statistically higher than that of BC (p < 0.001). After 12 months, all SARCs showed reduced SBS values and U100 showed values similar to those of SET and YCEM, and higher than those of BC and SC2 (p = 0.001). Demineralization pattern of SARCs was similar. At 24h, all SARCs showed no differences in the pH-value, except BC and U100 (p < 0.001). YCEM showed the highest Rp. U100, YCEM, and SC2 showed statistically higher FS (p<0.001) and E (p < 0.001) when compared with SET and BC. U100 and YCEM showed the best long-term bonding irrespective of the storage period. A significant reduction in SBS was found for all groups after 12 months. SBS was not shown to be correlated with physical-chemical properties, and appeared to be material-dependent. The polymerization profile suggested that an increased time of light activation, longer than that recommended by manufacturers, would be necessary to optimize DC of SARCs.